A eficácia social do direito ambiental no meio rural agrícola: uma análise a partir da lei 9.605/98 - Hüller, Chris Regina (2012)
Recently, the environmental issues has been growing as a matter of interest to society, This issues hits the right causing the number of laws on the subject to grown significantly in recent years. Nevertheless, within this universe are frequent juridical notes in the sense that the social effectiveness of these laws does not occur with the same intensity and enthusiasm with which they are promulgated. From an interdisciplinary proposal that seeks contributions of linguistics and sociology, this paper presents an approach to social issues regarding the effectiveness of environmental legislation in the rural environment considering a group of farmers penalized by the courts for violation of the provisions of Special Courts competence of Law 9.605/98 which deal with the flora. It initially made a theoretical approach under the theme of environmental sociology and Right seeking to understand and present the current status of discussions involving environmental legislation in the country. Following, based on Discourse Analysis, it is conducted an incursion by the legislative process that culminated in the promulgation of the Law 9.605/98, with emphasis on conflicting interests represented by the advocates of agribusiness and environmentalists in Congress. Afterwards, based on practical cases of application of the articles of Law 9.605/98 by the fiscalization and Justice aimed to know offenders penalized through a field survey, in order to characterize the farms, farming systems and production systems of existing farms. The data obtained were compared to those obtained in a similar group of farmers, environmentally adequated in order to produce inferences about the searched theme. Then, the same instrument applied to violators was applied to a group of similar farmers, but environmentally suitable in order to produce inferences about the search topic. The results obtained in this work demonstrated the model of development adopted in relation to agriculture is crucial to how the farmers understand environmental legislation. The research aimed to contribute to the debate about the effectiveness of environmental legislation in rural environment.